TLR2-Dependent Signaling for IL-15 Production Is Essential for the Homeostasis of Intestinal Intraepithelial Lymphocytes. (1st August 2016) - Qiu, Yuan; Pu, Aimin; Zheng, Hong; Liu, Minqiang; Chen, Weigang; Wang, Wensheng; Xiao, Weidong; Yang, Hua
Abstract : TLR2 signaling is related to colitis and involved in regulation of innate immunity in the intestinal tract, but the mechanisms remain unclear. The aim of this study is to investigate how TLR2 affects differentiation of intraepithelial lymphocytes (IELs) and regulates the susceptibility of colitis. IELs were isolated from the small intestine and colon of mice, respectively. The IEL phenotype, activation, and apoptosis were examined using flow cytometry and RT-PCR. IL-15 expression and IEL location were detected through immunohistochemistry. The experimental colitis was induced by administration of dextran sulfate sodium (DSS). We found that the numbers of CD8 αα +, CD8 αβ +, and TCR γδ + IELs were significantly decreased in TLR2-deficient mice and the residual IELs displayed reduced activation and proliferation and increased apoptosis, accompanied with impaired IL-15 expression by intestinal epithelial cells (IECs). Further study showed that TLR2 signaling maintained the expression of IL-15 in IEC via NF- κ B activation. Moreover, TLR2-deficient mice were found to be more susceptible to DSS-induced colitis as shown by the increased severity of colitis. Our results demonstrate that IECs contribute to the maintenance of IELs at least partly via TLR2-dependent IL-15 production, which provides a clue that may link IECs to innate immune protection of the host via IELs.